Nondescent vaginal hysterectomy: can it be a better alternative to abdominal hysterectomy - Kavita Mahadevappa; Preeth Kanwal; Naveen Prasanna (Barpeta Obstetrics and Gynaecological Society, 2021)
Objectives: Our study aims to compare the duration of surgery, amount of blood loss, duration of stay in the hospital, intraoperative and postoperative complications in total abdominal hysterectomy (TAH) and non descent vaginal hysterectomy (NDVH). Methods: A prospective study of 100 cases with uterine size less than 12 weeks requiring hysterectomy for benign diseases were randomly selected, 50 cases underwent NDVH and 50 cases underwent TAH. The outcome was analysed by chi-square test and paired t test. The p-value < 0.05 was considered significant. Results: The mean duration of surgery in NDVH was lesser than TAH [52.9mins (range 25-150 mins) Vs 60.6mins (range 30-120 mins)], which was not statistically significant. However mean blood loss, drop in haemoglobin, postoperative pain, early ambulation and postoperative stay were all lesser in NDVH when compared to TAH. This was statistically significant (p<0.05). There were no intraoperative complications like bowel, bladder and ureteric injury in both the groups. One patient of NDVH was converted to abdominal hysterectomy due to excessive bleeding. The postoperative complications were more in TAH than NDVH. Conclusion: Our study showed NDVH is a better option than abdominal hysterectomy for uterus less than 12 weeks with lesser operative time, blood loss and hospital stay and also have lesser intraoperative and postoperative complications.